2023
DOI: 10.1371/journal.ppat.1011109
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement amid genetic diversity in the Candida albicans biofilm regulatory network

Abstract: Biofilms of the fungal pathogen Candida albicans include abundant long filaments called hyphae. These cells express hypha-associated genes, which specify diverse virulence functions including surface adhesins that ensure biofilm integrity. Biofilm formation, virulence, and hypha-associated gene expression all depend upon the transcription factor Efg1. This transcription factor has been characterized extensively in the C. albicans type strain SC5314 and derivatives, but only recently has its function been explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Several recent studies have shown that gene disruptions can result in different phenotypes in different isolates of the same species [39][40][41] . Because our observation that C. parapsilosis Met4 is not the sole regulator of sulphur amino acid biosynthesis is surprising, we tested the effect of disrupting both MET4 and MET28 in different genetic backgrounds and in isolates from different C. parapsilosis clades 42 .…”
Section: Regulation Of Methionine Synthesis By Met4 and Met28mentioning
confidence: 99%
“…Several recent studies have shown that gene disruptions can result in different phenotypes in different isolates of the same species [39][40][41] . Because our observation that C. parapsilosis Met4 is not the sole regulator of sulphur amino acid biosynthesis is surprising, we tested the effect of disrupting both MET4 and MET28 in different genetic backgrounds and in isolates from different C. parapsilosis clades 42 .…”
Section: Regulation Of Methionine Synthesis By Met4 and Met28mentioning
confidence: 99%
“…We focused specifically on hypha-associated genes to determine whether the nrg1 Δ/Δ mutation affected these genes differently in the two strain backgrounds. We used a set of 152 genes derived from comparisons of strongly and weakly filamentous C. albicans strains ( 23 ). The P57055 nrg1 Δ/Δ mutant had downregulated RNA levels for 17 of the genes ( Fig.…”
Section: Observationmentioning
confidence: 99%
“…RNA-Seq, read mapping, and differential expression analysis using the DESeq2 R package (1.14.1) were performed by Novogene (Sacramento, CA), using three biological replicates per group ( Text S1 ). (A) Heat map representation of expression differences in 152 hypha-associated genes ( 23 ). Comparisons include P57055 nrg1 Δ/Δ versus P57055 WT (comparison 1), SC5314 nrg1 Δ/Δ versus SC5314 WT (comparison 2), P57055 WT versus SC5314 WT (comparison 3), and P57055 nrg1 Δ/Δ versus SC5314 nrg1 Δ/Δ (comparison 4).…”
Section: Observationmentioning
confidence: 99%
“…Efg1 is required for biofilm formation in multiple C . albicans clinical isolates [ 30 , 31 ], a feature that distinguishes it from other biofilm master regulators [ 30 ]. Efg1 controls expression of ~800 genes in any one strain [ 30 , 31 ], a lot to study effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Efg1 controls expression of ~800 genes in any one strain [ 30 , 31 ], a lot to study effectively. However, there is limited overlap among Efg1-regulated genes among clinical isolates [ 30 , 31 ], due in part to differences in expression of partner proteins that shape Efg1 outputs [ 32 ]. Only 110 genes are under Efg1 control in all 17 isolates we examined [ 31 ], a more manageable number of genes for functional analysis.…”
Section: Introductionmentioning
confidence: 99%